2008
DOI: 10.3402/ijch.v67i2-3.18282
|View full text |Cite
|
Sign up to set email alerts
|

The effect of UVB radiation on skin microbiota in patients with atopic dermatitis and healthy controls

Abstract: Objectives. To investigate Staphylococcus aureus and Staphylococcus epidermidis quantitatively in adult patients with atopic dermatitis and in healthy controls treated with UVB radiation. Study design. Twenty-three adult patients (of these, 3 were excluded) with flexural atopic dermatitis and 20 healthy controls were randomly selected at the outpatient clinic of the Dermatological Department, University Hospital, North Norway. Methods. Adult patients with atopic dermatitis (n=20) and healthy controls (n=20) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 21 publications
1
32
0
4
Order By: Relevance
“…The known mechanisms of action target immunomodulation through apoptosis of inflammatory cells, inhibition of Langerhans cells and alteration of cytokine production . In addition, UV has an antimicrobial effect reducing the colonization of S. aureus, due to its anti‐inflammatory effect and improves skin barrier . A different explanation could be supported by the role of Vitamin D: a recent study demonstrated that a 2‐week course of heliotherapy significantly improved vitamin D balance by increasing serum calcidiol concentration and caused a marked healing of AE .…”
Section: Phototherapymentioning
confidence: 99%
“…The known mechanisms of action target immunomodulation through apoptosis of inflammatory cells, inhibition of Langerhans cells and alteration of cytokine production . In addition, UV has an antimicrobial effect reducing the colonization of S. aureus, due to its anti‐inflammatory effect and improves skin barrier . A different explanation could be supported by the role of Vitamin D: a recent study demonstrated that a 2‐week course of heliotherapy significantly improved vitamin D balance by increasing serum calcidiol concentration and caused a marked healing of AE .…”
Section: Phototherapymentioning
confidence: 99%
“…Photo(chemo)therapy is a good therapeutic option to improve skin lesions, pruritus and sleeplessness in AD patients, with remission periods up to 6 months and no documented serious short‐term side‐effects . Phototherapy for AD might work due to several factors like the suppression of the antigen‐presenting function of the Langerhans’ cells, induction of antimicrobial peptides, the induction of apoptosis in infiltrating T cells, a reduction of the colonization by Staphylococcus aureus and Malassezia sp . and there may be a reduced antigen presentation by an increased phototherapy‐induced thickness of the stratum corneum leading to a milder AD …”
Section: Phototherapymentioning
confidence: 99%
“…Seasonality has been demonstrated in influencing diseases of the skin, likely as a result of microbiota alterations in response to climate changes (Jha and Gurung, 2006). Moreover, ultraviolet B (UVB) radiation, known to impact skin conditions, was observed to have disparate microbicidal effects on the skin microbiota (Dotterud et al, 2008). In particular, S. aureus appeared to be more sensitive to the radiation treatment than S. epidermidis .…”
Section: Driving Forces Of Human Skin Microbiota Diversitymentioning
confidence: 99%